2021
DOI: 10.1111/ijsa.12324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of response instructions on situational judgment test performance in operational selection and developmental contexts

Abstract: Susceptibility to faking is a key issue in the operational use of SJTs. We administered an SJT with both knowledge-based ("should do") and behavioral ("would do") response instructions in a low-stakes developmental context to 946 current medical residents and in a high-stakes selection context to 275 applicants to medical residency programs. Results indicated that (a) controlling for instruction condition, SJT scores were higher in the selection context and (b) controlling for context, SJT scores were lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Further research is also required to investigate the fakability and coachability of SJTs in selection contexts. 56,57 Finally, since SJTs typically have lower subgroup differences than measures with higher cognitive loading (e.g., the United States Medical Licensing Examination [USMLE]), 31,32 future research should examine how combining and differentially weighting SJT scores, USMLE scores, and other selection criteria might help to increase the diversity of minority applicants in programs’ rank pools. 58,59…”
Section: Discussionmentioning
confidence: 99%
“…Further research is also required to investigate the fakability and coachability of SJTs in selection contexts. 56,57 Finally, since SJTs typically have lower subgroup differences than measures with higher cognitive loading (e.g., the United States Medical Licensing Examination [USMLE]), 31,32 future research should examine how combining and differentially weighting SJT scores, USMLE scores, and other selection criteria might help to increase the diversity of minority applicants in programs’ rank pools. 58,59…”
Section: Discussionmentioning
confidence: 99%
“…Due to the selection context, SJTs are mostly conducted in a high-stakes setting. There is a lot of research comparing different aspects of high-stakes vs. low-stakes settings for SJTs (e.g., [ 29 , 30 ]). However, when conducting SJTs in a high-stakes setting, there can be various factors in addition to the actual processing of the test material that place additional demands on cognitive resources, such as a time limit.…”
Section: Introductionmentioning
confidence: 99%
“…In their meta‐analysis, McDaniel et al (2007) showed that SJTs with knowledge instructions correlate higher with cognitive ability, while SJTs with behavioral instructions correlate higher with personality. Furthermore, SJTs with knowledge instructions were less prone to faking in (high‐stakes) selection contexts (Nguyen et al, 2005; Zhang et al, 2021) due to their focus on maximum performance.…”
Section: Introductionmentioning
confidence: 99%